Peran Kharisma Sultan Agung dalam Keberlanjutan Tradisi Nguras Enceh di Makam Imogiri - Muhammad Ikhsan Ghofur; Tatik Khalifah (UIN Siber Syekh Nurjati Cirebon, 2024)
The nguras enceh tradition at the King's Tomb in Imogiri, Yogyakarta, reflects the community's belief in the extraordinary power of Sultan Agung, who is believed to bestow blessings through his legacy. This research uses a field method with a qualitative approach involving observation, interviews and documentation to understand the community's perception of the nguras enceh tradition. The results showed that the tradition has survived despite changes in some of its aspects, especially since the 2000s with the cultural carnival before the core event. The nguras enceh tradition is not only a form of respect for the ancestors, but also has social, cultural and economic functions. The charismatic influence of Sultan Agung is the main factor supporting the sustainability of this tradition, which attracts the enthusiasm of the community to participate each year. The procession of tahlil, prayer and taking of enceh water is carried out solemnly, showing deep respect for Sultan Agung. The community's participation in gotong royong activities and belief in the blessings of enceh water strengthen their social and spiritual values. Nguras enceh tradition is also a cultural and religious tourist attraction. In conclusion, the existence of the nguras enceh tradition at Imogiri Cemetery is based on the charismatic influence of Sultan Agung, which remains alive in various aspects of people's lives, strengthening their spiritual, social and economic ties to their ancestral heritage.